The Effect Of Sanyinjiao Acupuncture Therapy On The Primary Dysmenorrhea Scale In Nursing Students At The Faculty Of Health Sciences - Romadona Suci Ani; Sri Wulandari; Andria; Nana Aldriana (CV. AFDIFAL MAJU BERKAH, 2025)
Dysmenorrhea is pain in the lower abdomen during the menstrual cycle that does not cause abnormalities or uterine disease. Dysmenorrhea complaints are often complained of by women who can have an impact on emotional, psychological and health function. Dysmenorrhea interferes with the activities of adolescents who are in the process of learning at school. This causes adolescent girls to have difficulty concentrating because of the discomfort felt when experiencing dysmenorrhea. Adolescents who experience dysmenorrhea must be treated so that there are no worse impacts. The incidence of dysmenorrhea in Riau which has been studied in adolescent girls (age range 15 - 16 years) in Bangko District, Rokan Hilir Regency obtained a prevalence of dysmenorrhea of ​​95.7%. Research purpose : to determine whether there is an effect of Sanyinjiao point acupressure therapy on the scale of primary dysmenorrhea in undergraduate midwifery students at the Faculty of Health Sciences. Method: This type of research is quantitative with a pre-experimental research design with a pretest and posttest design approach using the NRS observation sheet. The sample in this study was 35 people. The sampling technique was a saturated sample. Data analysis used univariate and bivariate. Results: the results of the study showed that the average univariate analysis obtained an average pretest of 4.11 with a standard deviation of 1.231. While the average posttest was 2.40 with a standard deviation of 1.143. The results of the T-Test obtained a p value of 0.000 (p <0.05). This shows that there is a significant difference in the average dysmenorrhea scale before and after giving sanyinjiao to students of the S-1 Midwifery study program, Faculty of Health Sciences. Conclusion: With this research, it is hoped that it can add references or insight into sanyinjiao to reduce dysmenorrhea in adolescents.